2012
DOI: 10.1089/neu.2011.1934
|View full text |Cite
|
Sign up to set email alerts
|

Blast-Induced Tinnitus and Hearing Loss in Rats: Behavioral and Imaging Assays

Abstract: The current study used a rat model to investigate the underlying mechanisms of blast-induced tinnitus, hearing loss, and associated traumatic brain injury (TBI). Seven rats were used to evaluate behavioral evidence of tinnitus and hearing loss, and TBI using magnetic resonance imaging following a single 10-msec blast at 14 psi or 194 dB sound pressure level (SPL). The results demonstrated that the blast exposure induced early onset of tinnitus and central hearing impairment at a broad frequency range. The indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
88
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(99 citation statements)
references
References 123 publications
8
88
1
2
Order By: Relevance
“…52 The studies reported here, which were conducted using general anesthesia, however, suggest that a blast-related mTBI exposure can induce PTSD-related traits independent of exposure to a PTSD stressor. Unlike in some other studies, 5,26,31,33,34,36,38,43,[47][48][49][50] we did not see cognitive effects. No deficits were present in a Morris water maze or in a win-shift task, a relatively challenging test of working memory.…”
Section: Figcontrasting
confidence: 99%
See 2 more Smart Citations
“…52 The studies reported here, which were conducted using general anesthesia, however, suggest that a blast-related mTBI exposure can induce PTSD-related traits independent of exposure to a PTSD stressor. Unlike in some other studies, 5,26,31,33,34,36,38,43,[47][48][49][50] we did not see cognitive effects. No deficits were present in a Morris water maze or in a win-shift task, a relatively challenging test of working memory.…”
Section: Figcontrasting
confidence: 99%
“…23 Animals have been exposed to various forms of blast ranging from direct exposure to live explosives to controlled blast waves produced by compressed-air generators (reviewed in Elder et al 1 ) with activity in this area increasing dramatically in rodent models in recent years. 5, A number of studies have begun to look at the behavioral effects of blast across a range of blast exposures 5,26,31,33,34,36,38,43,[47][48][49][50] using blast alone or blast in combination with repeated stress 36 or other factors such as transportation or anesthesia. 33 These studies have documented a variety of, at least, short-term effects, suggesting that blast can be associated with anxiety as well as impairments in a variety of learning and memory tasks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that the LGB, the primary relay center for visual information, has never correlated with tinnitus in the literature, we speculate that our result may indicate the MGB rather than the LGB because of the possible spatial resolution problems with PET. Previous research on the MGB in murine tinnitus models has already elucidated changes in the spontaneous firing rates at a single-cell level, cell density reductions in all subdivisions by immunohistochemical staining, and significant damage and compensatory plastic changes using diffusion tensor imaging (26). Because of the anatomic subcortical location, the MGB has never been mentioned in tinnitus studies using qEEG or magnetoencephalography.…”
Section: Discussionmentioning
confidence: 99%
“…Auditory/vestibular injuries from blast traumatic brain injury (TBI) can cause increased incidence of tinnitus and hearing loss, which worsens over time if not treated [1][2][3][4]. Shock waves generated from explosive blasts are reported to be destructive to both gas-and fluid-filled structures of the body, including the lungs, intestines, brain, eyes, nose, and middle ear [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%